Project Finance for Business Development - Triantis, John (Ascent Audio, 2018)
Eliminating misconceptions about what is really important for successful project financings, Project Finance for Business Development shows you how to develop, structure, and implement projects successfully by creating competitive advantage. By shedding light on project finance failures, it also helps you avoid failures of your own. - Offers a roadmap for successful financing, participant roles and responsibilities, and assessing and testing project viability - Considers project finance from a broad business development and competitive advantage - Provides a strategic decision-forecasting perspective - Delves deeper than existing treatments of project finance into decisions needed to create and implement effective financing plans Helping readers develop, structure, and implement projects successfully by creating competitive advantage, this book is a useful tool for project sponsors and developers, helping them structure and implement projects by creating competitive advantage.